PENGGUNAAN TEMPLATE DIGITAL UNTUK MENYUSUN ELEMEN PEMASARAN ORGANISASI SECARA PRAKTIS DAN CEPAT - Widya Anggraini; Zuhrinal M. Nawawi (JOURNAL SAINS STUDENT RESEARCH, 2025)
The advancement of digital technology has transformed how organizations create and deliver marketing elements. This study aims to examine the effectiveness of using digital templates as a practical and fast solution for organizing marketing elements. The research method used is a literature review analyzing various studies related to digital marketing, graphic design, and digital template usage. The findings indicate that digital templates can accelerate the marketing material production process by up to 50%, maintain design consistency and quality, and significantly reduce production costs. Furthermore, the use of digital templates enhances organizational responsiveness to market changes and marketing trends, providing competitive advantages, especially for small and medium enterprises. However, successful implementation depends heavily on technological readiness, user training, and appropriate template selection. This study offers strategic recommendations for organizations to optimize digital template use in digital marketing strategies to support business growth and sustainability in the digital era.